Is selective thinning an adequate practice for adapting Quercus ilex coppices to climate change? - Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Joffre, Richard; Rambal, Serge (Annals of Forest Science, 2011)
& Introduction Future climatic scenarios demand an increasing involvement of management for forest preservation, but little is known on how forestry practices will benefit stands in facing variation of climatic components. & Objectives We investigated how selective thinning affected the response of an old Quercus ilex coppice to 6 years of throughfall reduction. Plots thinned from below (≈30% basal area removal) and unthinned plots were subject to either throughfall exclusion (TE; ≈33% throughfall reduction) or normal rainfall. Stem diameter growth, stem survival, and seed and sprout production were measured. & Results TE did not have a significant effect on stem growth but it reduced the production of viable acorns. Also, in the absence of thinning, TE accelerated the mortality of small stems and stimulated the emergence of new sprouts. Thinning reduced stem mortality, enhanced growth of residual stems, and caused a profuse emission of resprouts. Thinning also increased total seed production, but the crop had a large proportion of aborted seeds, especially in those areas subject to TE. & Conclusion The mere elimination of suppressed and diseased stems in abandoned Q. ilex coppice stands helps remaining trees to cope with current and future (probably longer and more intense) droughts. Potentially drier conditions might attenuate the success of thinning in producing a viable seed crop.
Keywords: Drought; forest adaptation strategy; seed production; sprouting; stem growth

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency

Resprouting of Quercus suber in NE Spain after fire - Pausas, J G (Journal of Vegetation Science, 1997)
Many Mediterranean species have evolved strategies that allow them to survive periodic wildfires. Quercus suber trees resprout after fire, some from stem buds and others from basal buds only. In the former case the canopy recovers quickly. In the latter case the stem dies but the tree survives and regrows from basal sprouts. The probability of stem death and the degree of height recovery were studied after a fire in a Q. suber forest in NE Spain using logistic regression analysis. The results suggest that most trees survive after fire; the probability of stem death is negatively related to tree diameter; and recovery is positively related to tree diameter and to bark thickness. Implication for management and conservation of cork-oak forests are discussed.
Keywords: Cork oak; disturbance; Mediterranean; sprouting